OPTIMASI FORMULA PATCH DAN UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL BIJI PEPAYA (Carica papaya L.) DENGAN KOMBINASI MATRIKS HPMC DAN PEG 400 TERHADAP Staphylococcus aureus - Tristina Yulianti; Dian Puspitasari; Didik Wahyudi (Jurnal Insan Farmasi Indonesia, 2021)
Acne is a skin disease caused by inflammation accompanied by blockage of skin and hair oil. One of the bacteria that cause acne is Staphylococcus aureus. Papaya seeds (Carica papaya L.) contain flavonoid, alkaloid and tanin which have been known to have antibacterial activity. Patch are an adhesive layer containing a drug, placed on the skin to deliver medication through the skin. The purpose of this study was to determine the combination of HPMC and PEG 400 which can provide a good antibacterial effect and to determine the evaluation of a good physical patch preparation. Extraction of papaya seeds using maceration method with 96% ethanol, and made 8 patch formulation. The physical properties included weight uniformity, folding endurance, thickness, and pH. The antibacterial activity test of the patch was carried out using the Kirby Bauer method. The data obtained were processed by statistical Analysis of Variance (ANOVA). The result of the research that the patch formula with a combination of HPMC 5,09 gram and PEG 4,91 gram had good characteristic. The result of the activity test for the etanol extract of papaya seeds (Carica papaya L.) against Staphylococcus aureus showed an average inhibition of 17,59 mm with a strong category.